Penggunaan Tone Indicator dalam Pencegahan Miskomunikasi di Media Sosial Twitter/X - Nugroho, Raudhia Aulia Putri; Sari, Ratna Permata (Program Studi Ilmu Komunikasi UII, 2024)
Miscommunication is common in text-based social media platforms like Twitter/X for a number of reasons. Misunderstandings may result from interactions that lack clear communication and tone of voice. As a result, tone indicators were created to represent the focus on tone in a text message. The aim of this research was to investigate the use of tone indicators and the effects they have on the audience. The analysis was conducted by investigating the audience's experience with tone indicators and the subsequent methods used to collect responses. The research employed a qualitative methodology. After using a purposive sampling strategy, seven informants were chosen. The study's findings demonstrated the value of tone indicators in social media communication on platforms like Twitter/X. When talking in a community, the audience or participants sense this tone indicator.